(untitled) (Jurnal Bina Praja, 2021)
The government has made many laws and regulations, but corruption issues cannot yet be controlled. Police and Prosecuting Attorney Institutions have not yet functioned effectively and efficiently in eradicating corruption. Therefore, the public hopes Komisi Pemberantasan Korupsi (KPK)/the Corruption Eradication Commission eliminates the crime. KPK is considerably appreciated by the public due to Operasi Tangkap Tangan (OTT)/Red-handed Catch Operation to many government officials involved in bribery action, but the subject matter thereof is whether the OTT is in line with the fundamental consideration of KPK founding pursuant to Law Number 30 of 2002 as updated by the Law Number 19 of 2019 in order to increase the eradication of corruption crime causing the state’s financial loss with respect to people welfare particularly KPK powers pursuant to the provision of Article 11 thereof, among others, specifying that KPK shall be authorized to conduct inquiry, investigation and prosecution on corruption crime related to the state financial loss of at least Rp 1,000,000,000 but in fact many OTTs performed by KPK have a value of hundred million Rupiah only and even there are any cases below Rp 100,000,000.-, and bribery action control through OTT being more dominant if compared to the state’s financial corruption is not in line with the primary consideration of KPK founding, and similarly the OTT below 1 billion Rupiah doesn’t conform to the provision of Article 11 thereof.